Trauma informed weight lifting: considerations for coaches, trainers and gym environments - Vigue, Dana; Rooney, Mariah; Nowakowski-Sims, Eva; Woods, Savannah (Frontiers in Psychology, 2023)
A growing body of research supports weight lifting as an effective adjunct intervention in the treatment of psychological trauma and trauma-related disorders. However, studies indicate that numerous barriers exist to participation in weight lifting, especially among populations disproportionately impacted by trauma. Trauma-informed care offers a paradigm for service delivery that aims to empower clients to access healing resources by attending to six domains of experience: safety, trustworthiness and transparency, peer support, collaboration and mutuality, empowerment, voice and choice, and cultural, historical, and gender issues. This mixed-methods study utilizes semi-structured, one-on-one interviews and surveys to inform the design of an evidence-based trauma-informed weight lifting program for trauma survivors. The contributions of this paper are twofold. First, the salient experiential categories for conceptualizing psychological healing in the gym environment are presented, informed by the lived experiences and recommendations of a national sample of trauma-impacted weight lifters. Second, based on the findings of this study, guidelines are proposed for the development of trauma-informed weight lifting programming that may be incorporated into the practice habits of personal trainers. The results of this study aid in the reduction in barriers that currently limit the adoption of weight lifting as an adjunct intervention for trauma and contribute to the professionalization of personal trainers in trauma-related competencies.